Target, tool, tenure and timing: the four T’s limiting the impact of traditional hunting in Indonesian Papua - Pattiselanno, Freddy; Ziembicki, Mark; Nasi, Robert; Krockenberger, Andrew (Frontiers in Conservation Science, 2024)
Subsistence hunting has sustained human populations in New Guinea for millennia, without seriously affecting the highest levels of biodiversity on Earth. Recent changes to hunting practices, demographic, social and economic context and the introduction of large exotic species has significantly altered the dynamic of hunting and its potential effects in north-west New Guinea. In this paper we examine contemporary hunting practices of six ethnic groups from highland to coastal sites throughout Papua and West Papua provinces of Indonesia. Semi-structured interviews were used to examine hunting practices as well as customary rules and attitudes associated with hunting in the region and how they have changed in living memory. Each group indicated traditional restrictions on at least one of target, tool, timing or tenure, albeit in varied ways. Six different hunting tools were used and each hunter typically combined several tools while hunting. Religious and cultural factors deeply influenced hunting practices among the communities. We discuss the implications of these findings and conclude with recommendations to integrate local, village level governance and customary practices with regional and national law for more effective conservation and management of wildlife in the region while simultaneously respecting cultural heritage and local ecological knowledge.